Pengaruh Kompetensi Sumber Daya Manusia, Pemberian Tunjangan Prestasi Kerja, Tekanan Kerja, dan Penerapan Sistem Pengendalian Internal Pemerintah Terhadap Kinerja Satuan Kerja Pemerintah Daerah (Studi Pada Kabupaten Pidie, Kabupaten Pidie Jaya, dan Kabupaten Aceh Utara) - Muhammad Arfan; Marhamah Marhamah (Program Magister Akuntansi Unsyiah, 2016)
This research was conducted at the Local Government Unit Districts of Pidie, Pidie Jaya, and Aceh Utara remember not optimal financial performance SKPD in the third district government which impact on the predicate opinions given by the CPC and ease of access in the data collection study included primary data and secondary. The purpose of this study was to see the influence of the quality of human resources, benefits administration job performance, work pressure, and the application of the system of internal control over the performance of SKPD. Samples numbered 62 on education in the district of Pidie, Pidie Jaya, and Aceh Utara totaling 62 respondents. The result of this research was there influence the quality of human resources, benefits administration job performance, work pressure, and the application of the system of internal control over the performance of SKPD either partially or simultaneously.KEYWORDS : the performance of local government unit (SKPD), competence of human resources, benefits administration job performance, work pressure, and the application of the system of internal control.